Tempting Fate Why Nonnuclear States Confront Nuclear Opponents - Avey, Paul C.; Project Muse. (Cornell University Press, 2019)
"Weak nonnuclear armed states have a number of strategies to win limited victories against nuclear armed opponents"--
The strategic logic of nuclear monopoly -- Iraq versus the United States -- Egypt versus Israel -- China versus the United States -- Soviet Union versus the United States.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Security, International -- Case studies; No first use (Nuclear strategy) -- Case studies; Nuclear weapons -- Government policy -- Case studies; Asymmetric warfare -- Case studies; Electronic books